ChemInform Abstract: Cold Sintering: A Paradigm Shift for Processing and Integration of Ceramics. Issue 47 (3rd November 2016) - Guo, Jing; Guo, Hanzheng; Baker, Amanda L.; Lanagan, Michael T.; Kupp, Elizabeth R.; Messing, Gary L.; Randall, Clive A.
Abstract: A new sintering technique (cold sintering) for ceramics and ceramic‐based composites using water as a transient solvent to effect densification at temperatures between room temperature and 200 °C is described.